New debt strategies after the brady plan - Walther Otremba (Intereconomics, 1989)
In view of the continuing debt problems of developing and industrialising countries there is a very real danger that a renewed downturn in the world economy could lead to a serious deterioration in relations between debtors and creditors, with far-reaching consequences for growth and employment in both industrial and developing countries. The task to be undertaken consists primarily in altering the basis for decision-making by both debtors and creditors in such a way that the rational strategy is effective action rather than inertia.
Keywords: 330; Indebtedness